Panorama of the civilization of the sustainable development - Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2021)
The article is about the conception of sustainable development settled in the context of culture and civilization changes. It can be taken as an alternative the further civilization development. The conception is a global strategy of the development. It relies on the inclusion of the natural environment into the social and economic development of a region, country, or in a global perspective, of the whole world. It assumes a long-lasting improvement of the quality of life of the present and future generations which is integrally associated with environmental improvement. It also shows the necessity of the spiritual growth and changes of the material aims of the development into immaterial ones. In all these aims and assumptions there are a lot of practical and mental problems in the sphere of sustainable development that retard and even make it impossible to put these conceptions effectively into life.